Ettekujutusi islami paradiisist ja paradiisineitsitest ning nende seos džihaadi ja märterlusega - Süld, Elo (Usuteaduslik Ajakiri, 2012)
Imaginations of Islam Paradise and Virgins of Paradise, and Their Relation to Jihad and Martyrdom In Islam, paradise is a promised reward both to the faithful and to martyrs who commit jihad. Hence, the descriptions of paradise must be such that people recognise them with their senses and start to long for it. The Koran and tradition describe paradise with the most compelling terms for goods and amenities of which a simple contemporary member of the then patriarchal society of Arab peninsula could dream of. Hence, the picture of paradise speaks to all human senses and sensory experiences. Also ḥūr’s are part of the luxury and joys of paradise. Their goal is to make paradise even more pleasing so that the exertion (and martyrdom) in one’s road of faith would be hallowed by a highly desirable goal. Sexuality is not excluded from paradise. Quite the opposite, it belongs to all the goods that are used for rewarding the faithful in paradise. Hence, the craving of martyrs for the paradise virgins becomes understandable.